Potential of Dry Leaf Waste as A Raw Material for Charcoal Briquettes Preparation as an Alternative Fuel - Sihotang, Muhammad Sontang; Sudiati; Aisyah, Dara (Talenta Publisher, 2024)
This research was motivated by the large potential of dry leaf waste in the campus environment of the University of North Sumatra and the awareness of the importance of appropriate innovation in the use of dry leaf waste as an environmentally friendly alternative fuel. The aim of this research was to determine the potential of leaf waste in the campus environment as a raw material for making environmentally friendly charcoal briquettes. The research method was observation, conducted in the campus environment of the University of North Sumatra, followed by calculating the amount of leaf waste produced per day, and testing continued with the production of dry leaf briquettes. The test results of the three combustions with different mixtures of raw materials in each combustion resulted in solid dry leaf briquettes that could ignite well. This study produced briquettes with proximate and ultimate tests that met SNI No.01-6235-2000 standards with a moisture content test of 4.35%, ash content test of 5.65%, carbon content test of 78.68%, calorific value of 6115 cal/g, and a burning rate of 1.5 grams/minute. Briquettes that meet SNI standards can become an environmentally friendly alternative energy source, a source of livelihood, and will certainly have a positive impact on waste management on the campus of the University of North Sumatra.